Analisis Faktor-Faktor Penunjang Kesiapan Pelaksanaan Rekam Medis Elektronik - Umar, William; Ginting, Chrismis Novalinda; Napiah, Ali (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the factors that support the readiness to implement electronic medical records at the Royal Prima Medan General Hospital. The research method uses cross-sectional. The results of this study indicate that there is an influence of the perception of benefits on the readiness of the implementation of electronic medical records at the Royal Prima Medan Hospital with a p-value = 0.041, there is an influence of behavioral interest factors using the behavioral attention hospital management information system on the readiness for the implementation of electronic medical records at the Royal Prima Medan Hospital with a p-value = 0.000, there is an influence of the use of the hospital management information system on the readiness of submitting electronic medical records at the Royal Prima Medan Hospital with a p-value = 0.016. The conclusion is that there is an influence of the perception of benefits, behavioral interest, and use of information systems on the implementation of electronic medical records is a behavioral variable. Keywords: Readiness for Implementation, Electronic Medical Records, Hospital